Work engagement: a theoric discussion - Porto-Martins, Paulo Cesar (2013)
Work engagement is considered as a positive cognitive state, of realization, related to the labour world, characterized by three dimensions: vigor, dedication and absorption. This construct is composed by a energetic-behavioral component (vigor), a emotional component (dedication), and a cognitive component (absorption). The objective of this study is to present a revision of the scientific international publications about the theme. The study of work engagement comes as a consequence of a numerous researches about the burnout syndrome, corroborating with the positive psychology premises. It’s concludes that there is a deficiency of publications about this construct, mainly in the Brazilian context.